2015
DOI: 10.1021/acs.jafc.5b03195
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Theaspirane and its Odorant Degradation Products in Hop and Beer

Abstract: In model oxidized media, six theaspirane-derived compounds were identified by gas chromatography-high resolution mass spectrometry: 4-hydroxy-7,8-dihydro-β-ionone, 6-hydroxy-7,8-dihydro-α-ionone, dihydrodehydro-β-ionone, two monoepoxides, and a derived alcohol. Only 4-hydroxy-7,8-dihydro-β-ionone and dihydrodehydro-β-ionone have been described previously in the literature. Investigation of hop revealed five of these compounds in free form together with theaspirane (especially in the Mosaic variety), while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Moreover, 7,8-dihydro-α-ionone is also abundant in some plants, such as Persicaria hydropiper [47] and Ecballium elaterium [48]. Furthermore, 7,8-dihydro-α-ionone is a phenolic compound and known to contribute to the plant's antioxidant effects [48,49]. Other abundant compounds (>2.4%) in S. purpurea-root-acetone (Table 5), i.e., 24-norursa-3,12-diene [50], α-amyrin [51], stigmast-5-en-3-ol [52], botulin [53], and 24-noroleana-3,12-diene also possess antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 7,8-dihydro-α-ionone is also abundant in some plants, such as Persicaria hydropiper [47] and Ecballium elaterium [48]. Furthermore, 7,8-dihydro-α-ionone is a phenolic compound and known to contribute to the plant's antioxidant effects [48,49]. Other abundant compounds (>2.4%) in S. purpurea-root-acetone (Table 5), i.e., 24-norursa-3,12-diene [50], α-amyrin [51], stigmast-5-en-3-ol [52], botulin [53], and 24-noroleana-3,12-diene also possess antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing GC-MS, 7,8-dihydro-α-ionone (Table 5) was the major compound present in S. purpurea-root-acetone. Moreover, 7,8-dihydro-αionone is a strong antioxidant [48,49]. Recent studies have demonstrated anti-proliferative-, anti-metastatic-, and apoptosis-induction properties of β-ionone, in vitro and in vivo [72].…”
Section: Discussionmentioning
confidence: 99%